(untitled) (Carte Romanze, 2015)
The Proemium in Historia Apollonii is a short introduction to the Historia Apollonii regis Tyri extant in two manuscripts from fourteenth-century Italy. It constitutes an unusual instance of medieval theorizing about the narrative structure of the genre of ancient romance. In this article I present the text of the Proemium, evaluate the evidence it provides about the circulation and reception of the Historia Apollonii, and raise the possibility that this text might lie behind Boccaccio’s description of the narrative structure of the stories recounted in Day Two of the Decameron.